Aberration correction in stimulated emission depletion microscopy to increase imaging depth in living brain tissue - Bancelin, Stéphane; Mercier, Luc; Murana, Emanuele; Nägerl, U. Valentin (Neurophotonics (Print), 2021)
Significance: Stimulated emission depletion (STED) microscopy enables nanoscale imaging of live samples, but it requires a specific spatial beam shaping that is highly sensitive to optical aberrations, limiting its depth penetration. Therefore, there is a need for methods to reduce optical aberrations and improve the spatial resolution of STED microscopy inside thick biological tissue. Aim: The aim of our work was to develop and validate a method based on adaptive optics to achieve an a priori correction of spherical aberrations as a function of imaging depth. Approach: We first measured the aberrations in a phantom sample of gold and fluorescent nanoparticles suspended in an agarose gel with a refractive index closely matching living brain tissue. We then used a spatial light modulator to apply corrective phase shifts and validate this calibration approach by imaging neurons in living brain slices. Results: After quantifying the spatial resolution in depth in phantom samples, we demonstrated that the corrections can substantially increase image quality in living brain slices. Specifically, we could measure structures as small as 80 nm at a depth of 90  μm inside the biological tissue and obtain a 60% signal increase after correction. Conclusion: We propose a simple and robust approach to calibrate and compensate the distortions of the STED beam profile introduced by spherical aberrations with increasing imaging depth and demonstrated that this method offers significant improvements in microscopy performance for nanoscale cellular imaging in live tissue.